Changes in Body Composition During Intensive Care Unit Stay and Outcomes in Patients with Severe COVID-19 Pneumonia: A Retrospective Cohort Study - Hayato Nakabayashi; Junko Yamaguchi; Ken Takahashi; Yasuyoshi Kai; Kosaku Kinoshita (Viruses)
This single-center retrospective observational study investigated the association between changes in body composition during hospitalization and outcomes in patients with severe coronavirus disease (COVID-19) pneumonia. Body composition was assessed using chest computed tomography (CT) within 3 days of intensive care unit admission and follow-up CT within 14 days. The study population comprised 89 adult patients, among whom 57 survived. The median APACHE II score on admission was 16. Initial CT scans showed that the iliopsoas muscle volume, sum of the pectoralis major and minor muscle areas, and erector spinae muscle (ESM) area were significantly larger in survivors than in non-survivors (p = 0.019, 0.011, and 0.001, respectively). Subcutaneous fat tissue (SAT) volume was higher in survivors (p = 0.003), and the rate of change in the SAT volume was lower in survivors (p = 0.043). Multivariate logistic regression analysis revealed that a high APACHE II score (OR: 0.834, 95% CI: 0.741–0.938, p = 0.002) and small ESM area (OR: 1.001, 95% CI: 1.000–1.002, p = 0.031) were independent predictors of mortality. In conclusion, the loss of supporting respiratory muscles, particularly ESM, may play a critical role beyond general acute sarcopenia, and the preserved SAT in non-survivors may reflect abnormal glucose metabolism due to severe inflammation.